Literature review on forest areas as a climate change strategy - Fajar, Fajar Darma Utama; Indah, Fitri Permata (Journal of Climate Change Society, 2024)
The purpose of reviewing the literature is how to design the concept of forest areas as a climate change strategy so that climate change is controlled. The method for creating an article is by reviewing the literature of each journal related to forest areas as a climate change strategy with a total of 30 journals. The results obtained from the literature review are that climate change depends on the amount of forest area, as evidence that almost every tree, especially trees that are protected forests, contains oxygen that functions to determine the temperature in the environment so that the more trees there are, the more stable the temperature and the condition of the environment is protected from the risk of natural disasters such as floods and landslides. The role in managing forest areas requires a concept of how to manage forests and care for them properly, especially for types of trees that are a source of oxygen that is useful for living things including humans. For this reason, in controlling the climate in the environment, it is necessary to maintain and preserve forests so that the climate can be controlled and the environment is more beautiful and improvements are needed in the management of forest areas so that the climate becomes stable